93.9k views
3 votes
12abx square - (9a square - 8b square)x - 6ab =0

User Edeline
by
6.3k points

1 Answer

2 votes

The value of x is
(3a)/(4b) and
-(2b)/(3a)

Step-by-step explanation:

The expression is
12abx^(2) -(9a^(2) -8b^(2) )x-6ab=0

Multiplying the term x withing the bracket, we get,


12abx^(2) -9a^(2) x+8b^(2) x-6ab=0

Grouping the terms, we have,


(12abx^(2) -9a^(2) x)+(8b^(2) x-6ab)=0

Taking out the common terms in each bracket, we get,


3ax(4bx -3a)+2b(4bx-3a)=0

Simplifying, we get,


(3ax+2b)(4bx -3a)=0

Equating each term to zero, we get,


\begin{aligned}3 a x+2 b &=0 \\3 a x &=-2 b \\x &=-(2 b)/(3 a)\end{aligned} and
\begin{aligned}4 b x-3 a &=0 \\4 b x &=3 a \\x &=(3 a)/(4 b)\end{aligned}

Hence, the values of x is
(3a)/(4b) and
-(2b)/(3a)

User AlanObject
by
6.3k points